Quantification of Operational Learning in Minimal Invasive Extracorporeal Circulation. Issue 7 (7th December 2016) - Anastasiadis, Kyriakos; Antonitsis, Polychronis; Asteriou, Christos; Argiriadou, Helena; Deliopoulos, Apostolos; Konstantinou, Dimitrios; Grosomanidis, Vassilios; Tossios, Paschalis
Abstract: Minimal invasive extracorporeal circulation (MiECC) has initiated important new efforts within science and technology towards a more physiologic perfusion. In this study, we aim to investigate the learning curve of our center regarding MiECC. We studied a series of 150 consecutive patients who underwent elective coronary artery bypass grafting by the same surgical team during the initial phase of MiECC application. Patients were randomly assigned into two groups. Group A ( n = 75) included patients operated on MiECC, while group B ( n = 75) included patients operated with conventional cardiopulmonary bypass (cCPB). The primary end‐point of the study was to identify whether there is a learning curve when operating on MiECC. The following parameters were unrelated with increasing experience, even though the results favored MiECC use: reduced CPB duration (102.9 ± 25 vs. 122.2 ± 33 min, P <0.001), peak troponin release (0.07 ± 0.02 vs. 0.1 ± 0.04 ng/mL, P < 0.01), peak creatinine levels (0.97 ± 0.24 vs. 1.2 ± 0.3 mg/dL, P < 0.001), duration of mechanical ventilation (14.1 ± 7.2 vs. 36.9 ± 59.8 h, P < 0.01) and ICU stay (2.1 ± 0.7 vs. 4.4 ± 6.4 days, P < 0.01). However, need for intraoperative blood transfusion showed a trend towards a gradual decrease as experience with MiECC system was accumulating ( R 2 = 0.094, P = 0.007). Subsequently, operational learning applied to postoperative hematocrit and hemoglobin levels ( R 2 = 0.098, P = 0.006). We identified that advantages of MiECC technology in terms of reduced hemodilution and improved end‐organ protection and clinical outcome are evident from the first patient. Optimal results are obtained with 50 cases; this refers mainly to significant reduction in the need for intraoperative blood transfusion. Teamwork from surgeons, anesthesiologists, and perfusionists is of paramount importance in order to maximize the clinical benefits from this technology.